The effect of bee propolis against Plasmodium berghel Infection in Swiss mice - Mahardika AW Mahardika AW (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Malaria is one of the most important parasitic disease and still as one of the world's public health problems among another tropical diseases.. One of the difficulty on controlling malaria is the resistance of malaria parasite to antimalaria drugs, therefore it is needed further researches to find alternative drugs of antimalaria. Propolis, a beehive product widely used in this folk medicine, has attracted the attention of researchers to elucidate its biological properties. Its anti-microbial properties are not confined to bacteria. Both in vitro and in vivo tests have shown propolis to be excellent in inhibiting the growth of many protozoa such as Trichomonas vaginalis and Giardia lamb/ia.Objective: This study was undertaken to know the propolis effect on Plasmodium berghei infection in Swiss miceMethods: Swiss mice were divided into 8 groups of 20 mice. Four groups were given 3.9 mg propolis orally every 2 days for two weeks before infection while the other four groups were not. Infection with P. berghei 1x107 was given intraperitoneally. Each four groups were treated after infection as follows : propolis , combination of propolis and chloroquine, chloroquine and none as negative control. Treatment with chloroquine injection was given within 3 days started at day-1 after infection with dose of 1.56, 1.56, and 0.8 mg. Treatment with propolis was given within 3 days also at dose of 3.9 mg/day. The effect of propolis was evaluated according to the percentage parasitemia counted every day started at day-1 after infection and the pathologic effect on the liver, spleen kidney and brain.Result: Propolis could not overcome the infection but inhibit the growth of Plasmodium in the erytrocytes and prolong life span of the mice. Pathologic affect propolis on the liver is mild inflammation while on the spleen, kidney and brain seems to inhibit organ damage.Conclusion: Those result showed the effect of propolis as an Immunomodulator.Key words: malaria - propolis - parasitemia - pathologic effect - immunomodulator.